NYADRAN SEBAGAI REALITAS YANG SAKRAL: PERSPEKTIF MIRCEA ELIADE - Aning Ayu Kusumawati (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2013)
The Modernists believe that human can only build himself thoroughly when he practices desacralization towards himself and moves to something profane, while the Traditionalists maintain that they are open for something sacred and should even achieve the stage of hierophanny that reveals chastity and eternity. This article explores the latter, however. It attempts to elaborate Eliade’s thought on a tradition in Java, namely Nyadran—one of the religious rituals or ways to respect and celebrate the spirits—as it presents the manifestation of the sacred or what Eliade calls as hierophanny. It discusses first about Mircea Eliade, particulary the critics and analysis on his works as well as the explanation on his views on the sacred and the profane and also on the myth and symbol; it then discusses Nyadran ritual itself in relation to Eliade’s conception.Keywords: sacred, profane, nyadran, symbols, myths